2014
DOI: 10.1038/onc.2014.138
|View full text |Cite|
|
Sign up to set email alerts
|

Gene expression profiling identifies FYN as an important molecule in tamoxifen resistance and a predictor of early recurrence in patients treated with endocrine therapy

Abstract: To elucidate the molecular mechanisms of tamoxifen resistance in breast cancer, we performed gene array analyses and identified 366 genes with altered expression in four unique tamoxifen-resistant (TamR) cell lines vs the parental tamoxifen-sensitive MCF-7/S0.5 cell line. Most of these genes were functionally linked to cell proliferation, death and control of gene expression, and include FYN, PRKCA, ITPR1, DPYD, DACH1, LYN, GBP1 and PRLR. Treatment with FYN-specific small interfering RNA or a SRC family kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…Analysis revealed that MCF-7 cells co-cultured with CD146 neg fibroblasts had increased expression of transcripts from 21 genes identified in the literature as up regulated in tamoxifen resistance (2632) (STable 2). Conversely, MCF-7 cells co-cultured with CD146 pos fibroblasts had increased expression of 15 genes identified in the literature as down-regulated in tamoxifen resistance (STable 3).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis revealed that MCF-7 cells co-cultured with CD146 neg fibroblasts had increased expression of transcripts from 21 genes identified in the literature as up regulated in tamoxifen resistance (2632) (STable 2). Conversely, MCF-7 cells co-cultured with CD146 pos fibroblasts had increased expression of 15 genes identified in the literature as down-regulated in tamoxifen resistance (STable 3).…”
Section: Resultsmentioning
confidence: 99%
“…37 We analyzed the correlation between SETD1A-dependent genes in MCF-7 cells and genes previously reported to have altered expression in Tam-R cells. Our analysis revealed that 12.2% of genes that were aberrantly expressed in Tam-R cells overlapped with SETD1A-dependent genes in MCF-7 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These data demonstrate that BASP1 regulates the expression of genes that are also regulated by ER α . Indeed, this group contains several known ER α target genes including BMPER, FHL1 and INHBB 15, 21, 22 (see Supplementary Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…Many breast cancers can present tamoxifen resistance and several studies have identified the gene expression changes that accompany this resistance but the underlying reasons are still not clear. 12, 13, 14, 15, 16 …”
mentioning
confidence: 99%